Distribution of dermal contamination under the influence of difference spraying flow rate among spray operator in tropical country - How, Vivien; Hashim, Zailina; Omar, Dzokhifli (IISTE, 2015)
Human skin is undoubtedly the major route of exposure to environmental contaminants, particularly when endo- and exo- pesticide drift is unavoidable whenever pesticide is applied. This field analytical study was conducted to determine dermal contamination of spray operator during pesticide application under the influence of difference spraying flow rate at the rice farming village of Selangor, Malaysia. The fluorescent tracer technique was used to quantify the dermal contamination pattern of the spray operator, followed by quantifying the concentration of fluoresceine with the aid of digital fluorometer. In summary, the mixture of pesticides applied to the farmland with higher spray rate (L/min) showed an increased contaminant doses retained on the body surface. In summary, it is recommended that changes in application techniques, setting up buffer zones or selection of low spraying flow rate (L/min) could improve the efficacy and safety of pesticide contamination through dermal pathway.